2017
DOI: 10.1103/physrevd.96.043003
|View full text |Cite
|
Sign up to set email alerts
|

Tau energy loss and ultrahigh energy skimming tau neutrinos

Abstract: We consider propagation of high-energy earth-skimming taus produced in interactions of astrophysical tau neutrinos. For astrophysical tau neutrinos, we take generic power-law flux, E −2 and the cosmogenic flux initiated by the protons. We calculate tau energy loss in several approaches, such as dipole models and the phenomenological approach in which parametrization of the F 2 is used. We evaluate the tau neutrino charged-current cross section using the same approaches for consistency. We find that uncertainty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The work of [44] included the full dependence on the y-distribution and concluded that the results can be reproduced accurately using only the average y as a function of energy. Between the models considered in [44], changes in y range from -3% to 7% at 10 15 eV and -15% to 23% at 10 20 eV. The resulting fluxes in that reference show consistent results with different models within 25%.…”
Section: Neutrino Interaction and Tau Energy-loss Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The work of [44] included the full dependence on the y-distribution and concluded that the results can be reproduced accurately using only the average y as a function of energy. Between the models considered in [44], changes in y range from -3% to 7% at 10 15 eV and -15% to 23% at 10 20 eV. The resulting fluxes in that reference show consistent results with different models within 25%.…”
Section: Neutrino Interaction and Tau Energy-loss Modelsmentioning
confidence: 99%
“…They give us an order of magnitude estimate of the uncertainties involved within the Standard Model. We note that alternative calculations based on the dipole model [44] [50]. The upper and lower curves represent the upper and lower limits of the uncertainties due to the parton distribution function.…”
Section: Neutrino Interaction and Tau Energy-loss Modelsmentioning
confidence: 99%
See 3 more Smart Citations